The organocatalytic synthesis of perfluorophenylsulfides via the thiolation of trimethyl(perfluorophenyl)silanes and thiosulfonates. Issue 42 (14th October 2021) - Luo, Jinyun; Lin, Muze; Wu, Leifang; Cai, Zhihua; He, Lin; Du, Guangfen
Abstract : The organic superbase t -Bu-P4 -catalyzed direct thiolation of trimethyl(perfluorophenyl)silanes and thiosulfonates was developed. Abstract : The organic superbase t -Bu-P4 -catalyzed direct thiolation of trimethyl(perfluorophenyl)silanes and thiosulfonates was developed. Yields of perfluorophenylsulfides of up to 97% under catalysis of 5 mol% t -Bu-P4 were achieved. This method was shown to provide an efficient way to construct the perfluorophenyl–sulfur bond under mild metal-free reaction conditions.